Exocytosis Proteins: Typical and Atypical Mechanisms of Action in Skeletal Muscle - Hwang, Jinhee; Thurmond, Debbie C. (Frontiers in Endocrinology, 2022)
Insulin-stimulated glucose uptake in skeletal muscle is of fundamental importance to prevent postprandial hyperglycemia, and long-term deficits in insulin-stimulated glucose uptake underlie insulin resistance and type 2 diabetes. Skeletal muscle is responsible for 80% of the peripheral glucose uptake from circulation via the insulin-responsive glucose transporter GLUT4. GLUT4 is mainly sequestered in intracellular GLUT4 storage vesicles in the basal state. In response to insulin, the GLUT4 storage vesicles rapidly translocate to the plasma membrane, where they undergo vesicle docking, priming, and fusion via the high-affinity interactions among the soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) exocytosis proteins and their regulators. Numerous studies have elucidated that GLUT4 translocation is defective in insulin resistance and type 2 diabetes. Emerging evidence also links defects in several SNAREs and SNARE regulatory proteins to insulin resistance and type 2 diabetes in rodents and humans. Therefore, we highlight the latest research on the role of SNAREs and their regulatory proteins in insulin-stimulated GLUT4 translocation in skeletal muscle. Subsequently, we discuss the novel emerging role of SNARE proteins as interaction partners in pathways not typically thought to involve SNAREs and how these atypical functions reveal novel therapeutic targets for combating peripheral insulin resistance and diabetes.